Pengaruh Yoga Hatha terhadap Siklus Menstruasi pada Remaja Putri di SMP N 1 Purwodadi - Ine Febrianti Suswardani; Raden Maria Veronika Widiatrilupi; Nila Widya Keswara (Universitas Malahayati Lampung, 2025)
ABSTRACT Teenage girls often experience menstrual cycle irregularities which are common conditions due to various factors, including psychological stress, unhealthy lifestyles, and hormonal imbalances in the body. Excessive stress can interfere with the production of reproductive hormones such as estrogen and progesterone, thus disrupting the menstrual cycle which should be regular. To overcome this, a non-pharmacological approach such as Hatha Yoga is one of the interventions that is easy to do and has been proven to help reduce stress levels, improve endocrine system function, and increase blood circulation which ultimately contributes to balancing hormones and regulating the menstrual cycle naturally. The results of a survey conducted in January 18, 2025 at SMP N 1 PURWODADI on 7th grade female adolescents found that there were students with irregular menstrual cycles. The type of quantitative research, with a pre-experimental research design with a pretest-posttest design approach. The population of all 7th grade female adolescents at SMP N 1 PURWODADI with purposive sampling. The study was conducted for 8 weeks with an intervention of 1 week 2 meetings with a duration of 30-45 minutes in 1 session. Data collection using questionnaires distributed to respondents. Data analysis was done univariately (frequency distribution) and bivariately (chi square). It is known that 6 (26.1%) respondents experienced menstrual cycle irregularities, respondents with menstrual cycle regularity were 17 (73.9%). There is an effect of hatha yoga on the menstrual cycle in 7th grade female adolescents at SMP N 1 PURWODADI with the results (p-value = 0.022). There is an effect of hatha yoga on the menstrual cycle in 7th grade female adolescents at SMP N 1 PURWODADI. Hatha yoga is one of the non-pharmacological methods that can overcome menstrual irregularities in female adolescents. Keywords: Yoga, Menstrual Cycle, Adolescent Girls, Reproductive Health, Non-Pharmacological ABSTRAK Remaja putri sering mengalami ketidakteraturan siklus menstruasi yang merupakan kondisi umum akibat berbagai faktor, termasuk stress psikologis, pola hidup yangtidak sehat, serta ketidakseimbangan hormon dalam tubuh. Stress yang berlebihan dapat mengganggu produksi hormon reproduksi seperti esterogen dan progesterone, sehingga mengacaukan siklus menstruasi yang seharusnya teratur. Untuk mengatasi hal tersebut, pendekatan non-farmakologisseperti Yoga Hatha menjadi salah satu intervensi yang mudah dilakukan dan terbukti dapat membantu menurunkan tingkat stress, memperbaiki fungsi sistem endokrin, serta meningkatkan sirkulasi darah yang pada akhirnya berkontribusi dalam menyeimbangkan hormon dan mengatur siklus menstruasi secara alami.Hasil survey yang dilakukan pada bulan Januari tanggal 18 2025 di SMP N 1 PURWODADI pada remaja putri kelas 7 diketahui adanya siswi dengan siklus menstruasi yang tidak teratur. Jenis penelitian kuantitatif, dengan rancangan penelitian pre-eksperimen dengan pendekatan design pretest-posttest. Populasi seluruh remaja putri kelas 7 di SMP N 1 PURWODADI dengan pengambilan sampel purposive sampling. Penelitian dilakukan selama 8 minggu dengan intervensi 1 minggu 2 kali pertemuan durasi 30-45 menit dalam 1 sesi. Pengambilan data menggunakan kuesioner yang dibagikan ke responden. Analisis data secara univariat (distribusi frequensi) dan biavriat (chi square). Diketahui sebanyak 6 (26.1%) responden mengalami ketidakteraturan siklus menstruasi, responden dengan keteraturan siklus menstruasi sebanyak 17 (73,9%), Terdapat pengaruh yoga hatha terhadap siklus menstruasi pada remaja putri kelas 7 di SMP N 1 PURWODADI dengan hasil (p-value = 0,022). Ada pengaruh yoga hatha terhadap siklus menstruasi pada remaja putri kelas 7 di SMP N 1 PURWODADI. Yoga hatha menjadi salah satu metode non-farmakologi yang dapat mengatasi ketidakteraturan menstruasi pada remaja putri. Kata Kunci: Yoga, Siklus Menstruasi, Remaja Putri, Kesehatan Reproduksi, Non-Farmakologis